2011
DOI: 10.1021/ci200083f
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitor and Substrate Binding by Angiotensin-Converting Enzyme: Quantum Mechanical/Molecular Mechanical Molecular Dynamics Studies

Abstract: Angiotensin-converting enzyme (ACE) is an important zinc-dependent hydrolase responsible for converting the inactive angiotensin I to the vasoconstrictor angiotensin II and for inactivating the vasodilator bradykinin. However, the substrate binding mode of ACE has not been completely understood. In this work, we propose a model for an ACE Michaelis complex based on two known X-ray structures of inhibitor-enzyme complexes. Specifically, the human testis angiotensin-converting enzyme (tACE) complexed with two cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
42
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 69 publications
(150 reference statements)
5
42
0
Order By: Relevance
“…The main interactions of the peptides were within the catalytic cavity with 8–12 amino acid residues, depending on the peptide, out of the total 38 amino acids comprising the catalytic cavity, and particularly with His353, known to play an important role in ACE activity. Zinc is essential for the activity of ACE, whose binding motifs are His383, Glu384, His387 and Glu411 . Molecular docking showed that the pure peptides interacted with His383 and Glu384, amino acids involved with zinc binding; thus this interaction potentially restrains ACE activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The main interactions of the peptides were within the catalytic cavity with 8–12 amino acid residues, depending on the peptide, out of the total 38 amino acids comprising the catalytic cavity, and particularly with His353, known to play an important role in ACE activity. Zinc is essential for the activity of ACE, whose binding motifs are His383, Glu384, His387 and Glu411 . Molecular docking showed that the pure peptides interacted with His383 and Glu384, amino acids involved with zinc binding; thus this interaction potentially restrains ACE activity.…”
Section: Resultsmentioning
confidence: 99%
“…Zinc is essential for the activity of ACE, whose binding motifs are His383, Glu384, His387 and Glu411. 43 Molecular docking showed that the pure peptides interacted with His383 and Glu384, amino acids involved with zinc binding; thus this interaction potentially restrains ACE activity.…”
Section: Ace Inhibition By Bpi Digests and Pure Peptides: Biochemicalmentioning
confidence: 99%
“…At present, QM/MM method and MD simulations have been combined to successfully study the inhibitorprotein interactions, functions of metalloproteins, and enzyme catalysis (Abdel-Azeim, Li, Chung, & Morokuma, 2011;Chen, Liang, Wang, Yi, Zhang, & Zhang, 2014;Duan, Mei, Zhang, Zhang, & Zhang, 2010;Duan, Mei, Zhang, & Zhang, 2009;Fan, Cembran, Ma, & Gao, 2013;Gao, Lu, Duan, Zhang, & Mei, 2011;Hou & Cui, 2013;Hou, McLaughlin, & Wang, 2007;Hu, Zhu, Zhang, Wang, & Zhang, 2010;Hu & Wang,2014;Ke, Wang, Xie, & Zhang, 2009;Keerthana & Kolandaivel, 2014;Meher, Kumar, & Bandyopadhyay, 2014;Smith, Ke, Guo, & Hengge, 2011;Wang et al, 2010Wang et al, , 2013Wang, Wu, Xu, Xie, & Guo, 2011;Wong, Richard, & Gao, 2009;Zhu, He, & Zhang, 2012;Zhu, Xiao et al, 2013). This method can take the polarizable electrostatic effect into account explicitly and accurately treat hydrogen bonding interactions.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its dual action, ACE inhibitors were one of the first line therapies in hypertensive and cardiovascular disorders for several years. [12][13][14][15][16][17][18][19][20][21][22][23] Very recently, Zhang C and coworkers 12 have suggested that the hydrolytic reaction of ACE proceeds via a general acid-base mechanism with the nucleophilic attack of a water molecule on the carbonyl carbon of the scissile bond. 3 In humans, there are two isoforms of ACE that are expressed from the same gene in a tissue-specific manner: the 140-kDa somatic form (sACE) that is found in a variety of tissues and the 77-kDa testicular form (tACE), which is exclusively expressed in germinal cells.…”
Section: Introductionmentioning
confidence: 99%
“…13,14 However, the ACE catalytic mechanism previously described only considers the tetra-coordinated configuration. 13,14 However, the ACE catalytic mechanism previously described only considers the tetra-coordinated configuration.…”
Section: Introductionmentioning
confidence: 99%